2015
DOI: 10.1007/978-3-662-47386-3_3
|View full text |Cite
|
Sign up to set email alerts
|

Distributed and Heterogeneous Data Analysis for Smart Urban Planning

Abstract: Abstract. Over the past decade, 'smart' cities have capitalized on new technologies and insights to transform their systems, operations and services. The rationale behind the use of these technologies is that an evidence-based, analytical approach to decision-making will lead to more robust and sustainable outcomes. However, harvesting high-quality data from the dense network of sensors embedded in the urban infrastructure, and combining this data with social network data, poses many challenges. In this paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…They stressed the necessity of implementing a complete smart campus decision support system based on the actual situation of each department of the university to ensure a more convenient learning and working environment for teachers and students. Oliveira et al [167] reported the result of a living campus experiment at the University of Melbourne (Australia), in which an intelligent middleware platform supports capture of distributed and heterogeneous environmental sensor data in outdoor public learning spaces. The up-to-date information reporting the use those spaces and users' routine combined to local perspectives offers new opportunities for better management and improved tools for planning and policymaking.…”
Section: Decision-making and Management Systemsmentioning
confidence: 99%
“…They stressed the necessity of implementing a complete smart campus decision support system based on the actual situation of each department of the university to ensure a more convenient learning and working environment for teachers and students. Oliveira et al [167] reported the result of a living campus experiment at the University of Melbourne (Australia), in which an intelligent middleware platform supports capture of distributed and heterogeneous environmental sensor data in outdoor public learning spaces. The up-to-date information reporting the use those spaces and users' routine combined to local perspectives offers new opportunities for better management and improved tools for planning and policymaking.…”
Section: Decision-making and Management Systemsmentioning
confidence: 99%